A High‐Performance Li–B–H Electrolyte for All‐Solid‐State Li Batteries. (14th February 2019) - Lu, Fuqiang; Pang, Yuepeng; Zhu, Mengfei; Han, Fudong; Yang, Junhe; Fang, Fang; Sun, Dalin; Zheng, Shiyou; Wang, Chunsheng
Abstract: Highly Li‐ion conductive Li4 (BH4 )3 I@SBA‐15 is synthesized by confining the LiI doped LiBH4 into mesoporous silica SBA‐15. Uniform nanoconfinement of P 63 mc phase Li4 (BH4 )3 I in SBA‐15 mesopores leads to a significantly enhanced conductivity of 2.5 × 10 −4 S cm −1 with a Li‐ion transference number of 0.97 at 35 °C. The super Li‐ion mobility in the interface layer with a thickness of 1.2 nm between Li4 (BH4 )3 I and SBA‐15 is believed to be responsible for the fast Li‐ion conduction in Li4 (BH4 )3 I@SBA‐15. Additionally, Li4 (BH4 )3 I@SBA‐15 also exhibits a wide apparent electrochemical stability window (0 to 5 V vs Li/Li + ) and a superior Li dendrite suppression capability (critical current density 2.6 mA cm −2 at 55 °C) due to the formation of stable interphases. More importantly, Li4 (BH4 )3 I@SBA‐15‐based Li batteries using either high‐capacity sulfur cathode or high‐voltage oxide cathode show excellent electrochemical performances, making Li4 (BH4 )3 I@SBA‐15 a very attractive electrolyte for next‐generation all‐solid‐state Li batteries. Abstract : A super ionic conductor Li4 (BH4 )3 I@SBA‐15 for all‐solid‐state Li batteries is reported. It shows a Li‐ion conductivity of 2.4 × 10 −4 S cm −1 at 35 °C and exhibits excellent electrochemical stability and electrode compatibility in the potential window of 0 to 5 V, as it can work well in Li–Li4 Ti5 O12, Li–S, and Li–LiCoO2 all‐solid‐state cells at 55 °C.